Regulation of calcium balance in the sturgeon Acipenser naccarii: a role for PTHrP - Fuentes, J. (2014)
Calcium regulation in sturgeon is of special interest because they are a representative of the ancient fishes possessing mainly cartilaginous skeletons and a supposedly low calcium demand. The present study aimed to characterize the effect of a chronic absence of dietary calcium and the effect of parathyroid hormone-related protein (PTHrPA) (1-34) (7) on calcium balance in juvenile sturgeon (Acipenser naccarii). At rest, sturgeon juveniles are in net positive calcium balance, since whole body calcium uptake is significantly higher than efflux and calcium accumulates in the body. To study the importance of dietary calcium, the sturgeon were kept on a calcium-free diet for 8 wk. This manipulation impaired growth as measured by failure to gain weight or increase in length and indicates that dietary calcium is important for growth in sturgeon. An increased whole body calcium uptake partially compensated dietary calcium deficiency and was associated with increased gill chloride cell number in lamellae and filaments in parallel with increased gill Na(+)K(+)-ATPase activity. In addition, a single injection of piscine PTHrP(1-34) significantly increased whole body calcium uptake and decreased whole body calcium efflux. Administration of PTHrP significantly increased circulating plasma calcium 4-24 h postinjection. The increase in net calcium transport and increased plasma levels of calcium is consistent with the actions of a hypercalcemic factor. It would appear that the sturgeon rely on calcium for growth and tightly regulate calcium transport. The action in calcium balance is consistent with PTHrP acting as a hypercalcemic factor in sturgeon.